(untitled) (INDIAN JOURNAL OF VOCATIONAL EDUCATION, 2023)
This research paper examines the impact of employability skills on employment and career success, with a specific focus on their relevance within industries. Employability skills, also known as soft skills or transferable skills, encompass a wide range of interpersonal communication, problem-solving, leadership, and teamwork abilities that enable individuals to thrive in the workplace and adapt to changing professional demands. The study employed a descriptive survey design to examine the influence of employability skills on employment and career success. A stratified random sampling technique was utilised to select a diverse sample of individuals from various industries. Data collection involved online surveys, and the questionnaire consisted of closed-ended and open-ended questions. Quantitative data were analysed using descriptive statistics, while qualitative data were subjected to thematic analysis. The methodology ensured the reliability and validity of the questionnaire through expert feedback and pilot testing. The study acknowledges limitations associated with self-report surveys but addressed them through rigorous sampling and analysis procedures. The results of this study reveal that communication skills, teamwork and collaboration, problem-solving and critical thinking, and time management are highly valued employability skills in the industry. Employers commonly use interviews, assessments, and reference checks to evaluate these skills during the hiring process. However, candidates entering the industry often lack proficiency in time management, digital literacy, and professionalism, indicating the need for skill development in these areas. These findings underscore the significance of continuous learning and adaptability for success in the industry. In conclusion, this research highlights the critical role of employability skills in employment and career success. It emphasises the need for individuals to develop and enhance skills such as communication, adaptability, teamwork, and continuous learning to meet the evolving demands of the industry.